The perceived effectiveness of traditional and faith healing in the treatment of mental illness: a systematic review of qualitative studies (2018)
Purpose: This work complements a quantitative review by Nortje et al. (Lancet Psychiatry 3(2):154–170, 2016) by exploring the qualitative literature in regard to the perceived effectiveness of traditional and faith healing of mental disorders. Method: Qualitative studies focusing specifically on traditional and/or faith healing practices for mental illness were retrieved from eight databases. Data were extracted into basic coding sheets to facilitate the assessment of the quality of eligible papers using the COREQ. Results: Sixteen articles met the inclusion criteria. Despite methodological limitations, there was evidence from the papers that stakeholders perceived traditional and/or faith healing to be effective in treating mental illness, especially when used in combination with biomedical treatment. Conclusion: Patients will continue to seek treatment from traditional and/or faith healers for mental illness if they perceive it to be effective regardless of alternative biomedical evidence. This provides opportunities for collaboration to address resource scarcity in low to middle income countries.